KEBIJAKAN SEKURITISASI PEMERINTAH INDONESIA DALAM MENANGGULAGI KASUS COVID-19 - Ahmad Saudi Ahmad (JURNAL PURNAMA BERAZAM, 2022)
The covid-19 virus has had an impact on the policies of countries in the world, including Indonesia, by responding to covid-19 cases with securitization policies. This study aims to analyze what are the securitization policies of the Indonesian government in responding to cases of covid-19 that can threaten the security of the Indonesian people. This study uses qualitative research methods with data collection techniques from library research and data sources from books, journals, websites and newspapers that are relevant to the topic of this research. The results of this study indicate that the Indonesian government has a securitization policy in response to the spread of the covid-19 virus.